Novel Soft Switching Isolated Dc-Dc Converters Topologies - Charin, Chanuri (2013)
DC-DC converters are widely used in many applications such as power supplies, PV system, renewable energy systems and industrial applications. One of the main problems in dc-dc converters is the switching loss which affects efficiency and also the power density of the converter. To alleviate the switching loss problem this thesis proposes novel soft switching PWM isolated dc-dc converters topologies. Three topologies of dc-dc converters are presented in this thesis. These are half-bridge dc-dc converter with auxiliary circuit, full-bridge dc-dc converter with multilevel inverter leg and full-bridge dc-dc converter with auxiliary circuit. The proposed half bridge dcdc converter with auxiliary circuit is designed and tested both with diode bridge rectifier and centre-tapped transformer rectifier. The proposed converters are designed and evaluated in term of soft switching. Soft switching operations are achieved by charging and discharging process of the flying capacitor. In proposed topologies, all the power switches operate under soft-switching conditions. Therefore, overall switching loss of the power switches is greatly reduced. The output voltages of the converters are varied by PWM control. The effectiveness of the new converters topologies is evaluated both by simulation and experimental results of a laboratory scale down prototype. The obtained experimental results are found in good agreement with the simulation results. The proposed half-bridge dc-dc converter with auxiliary circuit and centre-tapped transformer rectifier has highest efficiency among all the proposed topologies. Its efficiency is 81% at the output power of 25W, so it is considered best among all the proposed topologies.